INTEGRATION OF BACTERIAL BIOPESTICIDE DIPEL AND NEEM PESTICIDE FYTOMAX IN CONTROL TOMATO MOTH Tuta absoluta ON THREE VARIETIES OF TOMATOES UNDER THE PLASTIC HOUSE CONDITIONS - Baker, Safaa Zakaria (Diyala Agricultural Sciences Journal, 2018)
Laboratory and field experiments were conducted to study compatibility and integration bacterial bio pesticide (Dipel) and neem formulation (Fytomax) in control the tomato moth Tuta absoluta on three varieties of tomatoes (Tamara, Shahera and Dania) under the plastic house conditions. Laboratory results showed that Fytomax at the half field rate (Fr - 50%) was more compatible with Dipel, which achieved the lowest reduction percentage in the number of colonies of bacteria B. thuringiensis var kurstak amounted to 6.3% compared with the reduction percentage to 15.36% at field rate (Fr), while the higher concentration (Fr + 50%) inhibited the growth of bacteria, reduction percentage was 65.35%. Field results showed the integration of Dipel and Fytomax and Dania tomato variety in control the larvae of a tomato moth Tuta absoluta, the combination treatment (Fytomax + Dipel) at half-field rate (Fr- 50%) on Dania tomato variety was superiority with highest mortality percentage of larvae was 80.32%, while the lowest mortality percentages were at two treatments Fytomax and Dipel were 29.16 and 29.52% respectively. Results showed that mortality percentages increased with the passage of time as a combination (Fytomax + Dipel) achieved highest mortality percentages of larvae at half-field rate( Fr - 50% ) were 38.77, 87.51 and 91.43 after 1, 3 and 7 days from treating respectively.